Agricultural development planning project - Ghana. Meat Development Project - Cockcroft, F.L. (1977)
Feasibility study report of meat development project in Ghana. The performance of the project was evaluated and possible suggestions made on how to increase production and supply of poultry, eggs, pig and sheep to eliminate their imports. Technical, managerial and financial implications of the project were assessed and proposed levels of contribution indicated.